P90 Complementary role of 18F- FDG PET/CT for sentinel lymph node algorithm in endometrial cancer with high risk factors for lymphatic metastasis. (1st November 2019) - Taşkin, S; Varli, B; Ersöz, CC; Altin, D; Soydal, Ç; Ortaç, F
Abstract : Introduction/Background: National Comprehensive Cancer Network (NCCN) sentinel lymph node (SLN) algorithm includes 'mandatory steps' for evaluating pelvic lymph nodes but assessment of paraaortic area is left to surgeon's discretion. In this study we aimed to investigate the complementary role of preoperative 18 F- FDG PET/CT scan in detecting pelvic and especially paraaortic lymphatic metastasis in endometrial cancer patients with high risk factor(s) according to Mayo Clinic Criteria and underwent SLN algorithm. Methodology: Patients who underwent preoperative 18 F- FDG PET/CT scan, intraoperative SLN algorithm followed by systematic lymphadenectomy and had at least one high risk criterion for lymphatic metastasis were included in this study. 18 F- FDG PET/CT and SLN algorithm were compared with final histopathological results of systematic lymphadenectomy. Results: 38 patients were eligible for the study. Lymphatic metastasis was seen in 10 patients (26.3%). 4 cases had paraaortic lymphatic metastases which were together with pelvic (n:2) or isolated (n:2) metastases. SLN algorithm was able to detect all pelvic lymph node metastases. However isolated paraaortic metastases were diagnosed only by 18 F- FDG PET/CT. In 76 hemipelvises, sensitivity and negative predictive value of SLN algorithm for diagnosis of pelvic nodal metastasis were 100%, while sensitivity, specifity, positive predictive value and negative predictive value of 18 F- FDG PET/CT were 45.4%, 95.3%, 62.5% and 91.1%, respectively. Conclusion: Although SLN algorithm has an excellent diagnostic value for pelvic nodal metastasis, paraaortic metastasis might be under-diagnosed. 18 F- FDG PET/CT may be a feasible tool to exclude paraaortic lymphatic metastasis in high risk patients for lymphatic metastasis who will undergo SLN algorithm. Disclosure: Nothing to disclose.